Geopolitical dimensions to build a dam on the downstream Renaissance (Egypt and Sudan) (Journal of the College of Education for Women, 2019)
Varied uses of international rivers in the past few decades dramatically, resulting in this multiplicity of uses and all associated with it for the occurrence of freshwater scarcity activities, and thus an increase in conflicts and disputes around on the rights of each of the riparian countries to benefit from the waters of the river at various purposes, particularly the establishment of dams on some of them as is the case (Renaissance Ethiopian) big impact on downstream countries Dam (Egypt and Sudan), due to the Oukuahma at the end of the Nile Valley made them vulnerable to environmental fluctuations, political crises facing the Nile basin countries, and any reduction in the proportion of water is not only the Nile River, but for all rivers will have serious repercussions, affecting the agricultural and industrial production, food security, particularly Egypt as it exploits (85%) of the river water for agricultural purposes, and thus water share to be below the required threshold, so unlike all the other Nile basin countries that have many other sources so is the subject of the Nile water for Egypt is a national security issue in the absence of a comprehensive agreement includes all the riparian states of the Nile River, especially with the presence of external forces (such as the US and Israel) are trying to provoke differences in order to become a party to take advantage of the territorial waters and international, which will cause adverse effects (current and future) to downstream (Egypt and Sudan), represented by (water deficit grave) will happen by filling the tank with water period, and after the collapse of the dam being built on an extremely rugged slope on the plateau, the prospects for its collapse is very high.